2013
DOI: 10.1016/j.eneco.2013.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the diffusion of renewable energy technology in developing countries

Abstract: In this paper we study the diffusion of non-hydro renewable energy (NHRE) technologies for electricity generation across 108 developing countries between 1980 and 2010. We use two-stage estimation methods to identify the determinants behind the choice of whether or not to adopt NHRE as well as about the amount of electricity to produce from renewable energy sources. We find that NHRE diffusion accelerates with the implementation of economic and regulatory instruments, higher per capita income and schooling lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
127
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(168 citation statements)
references
References 58 publications
19
127
1
Order By: Relevance
“…Typically, our finding is not in line with recent studies by Rafindadi and Ozturk (2016) and, Bento and Moutinho (2016) indicate that trade openness (exports and imports) has a causal relationship with electricity consumption. Similar cases were found from empirical studies by for China, and Pfeiffer and Mulder (2013) for numbers of developing countries, where increases in trade will delay renewable energy consumption (electricity). The impact of dummy variable has negative and significant impact on electricity demand.…”
Section: Resultssupporting
confidence: 76%
“…Typically, our finding is not in line with recent studies by Rafindadi and Ozturk (2016) and, Bento and Moutinho (2016) indicate that trade openness (exports and imports) has a causal relationship with electricity consumption. Similar cases were found from empirical studies by for China, and Pfeiffer and Mulder (2013) for numbers of developing countries, where increases in trade will delay renewable energy consumption (electricity). The impact of dummy variable has negative and significant impact on electricity demand.…”
Section: Resultssupporting
confidence: 76%
“…They showed that the aversion to policy risk is more pronounced among investors who hold strong individualistic worldviews and thus prefer "free markets" rather than government intervention. These views are different to that of Pfeiffer & Mulder (2013) who discovered that renewables diffusion accelerates with the implementation of economic and regulatory instruments. Nesta et al (2014) found a significant effect of energy market liberalisation on innovation in RE technologies implying that, given the characteristics of the energy market, in which the core competences of the incumbent are generally tied to fossil fuel plants whereas the production of RE is mainly decentralised in small-sized units, the entry of non-utility generators made possible by market liberalisation increases the incentives for renewables.…”
Section: Country Specific Factorsmentioning
confidence: 60%
“…However, Aguirre & Ibikunle (2014) imply that energy use is negatively linked to RE participation, stating that under high pressure to ensure the energy supply, countries with increasing energy requirements are inclined to pursue more fossil fuel solutions and other cheap alternatives instead of renewables to cover electricity demand. This view is shared by Pfeiffer & Mulder (2013) who suggested that growth of electricity consumption appears to delay RE diffusion.…”
Section: Socioeconomic Factorsmentioning
confidence: 90%
“…For instance, higher-income countries could afford to invest in greater levels of electricity infrastructure and to have higher consumption levels. For a component of total electricity use, Pfeiffer and Mulder [45] find that non-hydro renewable electricity is promoted by higher per capita income. In relation to analysis of household data from Mexico, Gertler et al [46] suggest a nonlinear Engel curve with purchase of energy-using assets being much more likely above income thresholds.…”
Section: Methods and Datamentioning
confidence: 99%